Coaching for human development and performance in sports (Springer Nature, 2020)
This book addresses important topics of coaching in order to better understand what sports coaching is and the challenges that arise when assuming this activity. It provides the reader with useful insights to the field of sports coaching, and discusses topics such as coaching education, areas of intervention, and main challenges. With contributions by experts and well-known authors in the field, this volume presents an up-to-date picture of the scholarship in the coaching field. It introduces key aspects on the future of the science of coaching and provides coach educators, researchers, faculty, and students with new perspectives on topics within the field to help improve their coaching effectiveness. Verlagsinfo